Penerapan Metode Tutor Sebaya dalam Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Belajar Peserta Didik - Minangsari, Ratih Permata; Rachmawati, Rivanna Citraning; Wardani, Susilo (Universitas PGRI Semarang, 2025)
We expect the application of the Problem-Based Learning (PBL) model to improve students' learning outcomes through a student-centered approach. However, the varying levels of student comprehension often pose challenges for teachers in creating effective learning. The peer tutoring method can serve as an alternative learning strategy to address this challenge, where more competent students assist their peers who have difficulty understanding the learning material. This study aims to examine the improvement of students' learning outcomes through the implementation of the peer tutoring method in problem-based learning. This research is Classroom Action Research (CAR). The subjects of the study were 34 students of class XI ATPH A at SMK Negeri 1 Bawen. Data were collected using interviews, observations, and documentation. The data analysis method employed was qualitative descriptive analysis. The results showed significant improvement in learning outcomes, with the mastery level increasing from 59% in the first cycle to 100% in the second cycle. Students from the less skilled group showed increased courage to ask questions and engage in discussions with their peer tutors, while tutors from the more skilled group experienced reinforced understanding and boosted self-confidence. These results indicate that the integration of the peer tutoring method in problem-based learning is not only effective in improving learning outcomes but also facilitates collaboration and social interaction among students, creating an inclusive learning environment.